Fertility preservation in male cancer patients. Counseling and reproductive outcomes - Kimelman, Dana; Torrens, Andrea; Bonelli, Carla; Sapiro, Rossana (Frontiers in Cell and Developmental Biology, 2023)
Advances in cancer treatments have determined an increase in survival rates. However, these lifesaving therapies may have a negative impact on reproductive health. To diminish the infertility risk; different fertility preservation strategies have been designed. Sperm freezing is the gold standard fertility preservation method in the case of post-pubertal men. The main objective of this study is to evaluate the fertility status of Uruguayan male cancer survivors who have gone through sperm freezing, as well as to assess oncofertility counseling received by these patients. This is a descriptive, cross-sectional, observational, and transversal study. A survey was conducted on male cancer survivors who cryopreserved sperm between 1985 and 2021 in “Reprovita Lab and Biobank” which is the only sperm bank in this country. One hundred thirty-five participants answered the survey. At the time of diagnosis, the mean age of patients was 28.8±6.4 years old. Testicular was the most frequent type of cancer (64 %). Only, 12% (n=15) already had children at the time of diagnosis. Among the interviewed survivors, 50% (n=62) attempted to conceive after cancer treatment, and 68% (n=42) achieved natural pregnancy. Patients who did not achieve spontaneous conception (n=11), used their cryopreserved samples, and 45.4% achieved pregnancy. About 86% (n=107) of survivors believed that the timing of oncofertility referrals was appropriate and 97% considered that having the possibility of protecting their fertility was very important. Eighty percent (n=101), were advised by their attending physicians, 14% (n=18) sought advice from family members or friends, and 4% (n=5) from oncofertility specialists. To our knowledge, this is the first study evaluating the reproductive outcomes of male cancer survivors in our country and the region. Most of the interviewed survivors considered fertility preservation as a positive initiative, independent of their reproductive outcomes, reflecting the importance of fertility preservation counseling as one of the most important aspects for future quality of life of young cancer patients.